Limited health literacy is associated with poorer clinical outcomes in elderly with type 2 diabetes mellitus - Yilmazel, Gulay; Cici, Remziye (Faculty of Medicine, Trisakti University, 2019)
BackgroundDiabetes mellitus is a significant global public health concern. Poor knowledge of disease and healthcare utilization is associated with poor health outcomes, leading to increasing burden of diabetes in many developing countries. The present study aimed to assess diabetes health literacy and clinical outcomes in elderly patients registered to the home health agency. MethodsA cross-sectional study was conducted in the city of Ã‡orum, Turkey, with 160 type 2 diabetic patients of both sexes and aged between 50-91 years. To identify health literacy, the Rapid Estimate of Adult Literacy in Medicine test was administered to the patients. Clinical parameters were based on routine medical examinations by measuring blood pressure levels, glycosylated hemoglobin, and lipoprotein levels. In order to identify the risk of depression, the Beck Depression Scale was used. ResultsOf the patients, 85.0% had limited health literacy. The majority of patients (95.0%) had poor glycemic control and limited health literacy was associated with having high level of HbA1c (p<0.05). Adequate health literacy was associated with regular foot care (p<0.05). Also patients with limited health literacy were more likely to have depression (p<0.001). Limited health literacy increased the risk of poor glycemic control (OR=6.82;95% CI=1.34-9.78) and retinopathy (OR=6.91;95% CI=1.23-9.44). ConclusionLimited health literacy is consistently associated with poorer diabetes clinical outcomes in elderly type 2 diabetes melltius Contents of diabetes education should be arranged according to patientsâ€™ health literacy level which requires visual and auditory teaching materials for patients with limited health literacy.